Arabidopsis subtilase SASP is involved in the regulation of ABA signaling and drought tolerance by interacting with OPEN STOMATA 1. (1st June 2018) - Wang, Qianqian; Guo, Qianli; Guo, Yuanyuan; Yang, Jieshu; Wang, Min; Duan, Xiaoke; Niu, Jiayu; Liu, Shuai; Zhang, Jianzhen; Lu, Yanke; Hou, Zhi; Miao, Wei; et al.
Abstract : A new role of SASP in regulating ABA signaling and drought tolerance through interaction with OST1 is determined, which is distinct from its involvement in leaf senescence as previously reported. Abstract: Arabidopsis Senescence-Associated Subtilisin Protease (SASP) has previously been reported to participate in leaf senescence and in the development of inflorescences and siliques. Here, we describe a new role of SASP in the regulation of abscisic acid (ABA) signaling. SASP encodes a subtilase and its expression was considerably induced by darkness, ABA, and ethylene treatments. sasp knockout mutants displayed obvious developmental phenotypes such as early flowering and smaller leaves. In particular, the sasp mutants exhibited enhanced ABA sensitivity during seed germination and seedling growth, heightened ABA-mediated leaf senescence, and increased production of reactive oxygen species (ROS). Importantly, the sasp mutants also showed remarkably increased tolerance to drought, with expression of six ABA signaling-related genes being either up- or down-regulated following ABA treatment. Interaction assays demonstrated that SASP physically interacts with OPEN STOMATA 1 (OST1) at the cell periphery. Co-expression of SASP and OST1 led to degradation of OST1, whereas this degradation was impaired in sasp-1 protoplasts. ROS attenuation assays demonstrated that in sasp-1 mutant guard cells the attenuation rate markedly decreased. Taken together, the results demonstrate that SASP plays an important role in regulating ABA signaling and drought tolerance through interaction with OST1.